2020
DOI: 10.1186/s12889-020-09022-8
|View full text |Cite
|
Sign up to set email alerts
|

Leisure time physical activity and depressive symptoms among adolescents in Sweden

Abstract: Background: Mental health problems have increased noticeably among adolescents. Physical activity has been identified as an important factor in the promotion of mental health. The purpose of this study was to explore how leisure time physical activity was associated with depressive symptoms among adolescents in Sweden. Methods: Using binary logistic regression we analyzed Swedish data collected as part of the Children of Immigrants: Longitudinal Survey in Four European Countries. The complete sample used for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…There is abundant evidence that the antidepressant effects could emerge with non-medical intervention represented by leisure-time physical activity (LPA) in teenagers' ( 9 11 ), middle-aged ( 12 ) and elder ( 13 15 ) groups. A recent meta-analysis, which included 49 unique prospective cohort studies and 266,939 participants, found that people with high levels of physical activity had lower odds of developing depression compared with low levels (adjusted OR = 0.83, 95% CI: 0.79 ~ 0.88; I 2 = 0.00) ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is abundant evidence that the antidepressant effects could emerge with non-medical intervention represented by leisure-time physical activity (LPA) in teenagers' ( 9 11 ), middle-aged ( 12 ) and elder ( 13 15 ) groups. A recent meta-analysis, which included 49 unique prospective cohort studies and 266,939 participants, found that people with high levels of physical activity had lower odds of developing depression compared with low levels (adjusted OR = 0.83, 95% CI: 0.79 ~ 0.88; I 2 = 0.00) ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hobbies such as sports and arts generally associate with positive mental health of those involved [20,21]. Children and adolescents with active leisure time activities have been documented to have fewer psychological symptoms than their peers without these activities [22][23][24]. People's behavior and perception of themselves is widely linked to those social groups, where they belong.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents who participated in physical activities in their free time daily, weekly, or monthly were substantially less likely to feel frequently depressed than those who were physically inactive (Ma, 2020).…”
Section: Charlotte Mckercher 2013mentioning
confidence: 89%
“…Li Ma, 2020 The aim of this study was to explore how leisure-time physical activity was associated with depressive symptoms among adolescents in Sweden.…”
Section: Charlotte Mckercher 2013mentioning
confidence: 99%